PENERAPAN PEMBERIAN PENGUATAN (REINFORCEMENT) DALAM PEMBELAJARAN BACA AL-QUR’AN DI TK AL AZHAR 28 SOLOBARU, SUKOHARJO TAHUN 2016/2017 - Rahmawati, Putri Rizqiyah (El-Hayah, 2018)
Abstract : Facts about the lack of teachers and school’s knowledge on the importance of providing reinforcement as a motivator for children to better achievement in learning is a background of this research. In the middle of the lack of knowledge of the importance of providing reinforcement, Al-Azhar 28 Kindergarten Solo Baru Sukoharjo actually apply the optimal reinforcement in learning, especially learning to read Al-Qur'an for students. It becomes interesting to examine, because the concept of reinforcement is doing by all teachers and executed consistently. Of course there is a large role of policy makers who make this reinforcement activity suistainably. This reinforcement activity is given personally, each child will get the reinforcement one by one. The purpose of this research is to know the forms of reinforcement that applied in Al-Azhar 28 Kindergarten Solo Baru and the role of the school represented by the headmaster and parents in this activity.This research is a qualitative descriptive research with subject research are headmaster and special teacher in learning to read Al-Qur'an. Data collection is done by observation, in-depth interview, and documentation. Researchers used the method of triangulation of sources and methods as a technique of data validity. Data analysis techniques used are interactive analysis by Miles and Huberman, analysis activities include ; data reduction, display data, and conclusion drawing / verification.The results showed that the application of reinforcement in learning to read Al-Qur'an in Al-Azhar 28 Kindergarten Solo Baru in verbal and non verbal forms. There is a reinforcement with fun activities in learning to read the Al-Qur'an. This activity can increase the motivation of children to be able to read al-qur'an, it can be seen from the increasing number of children who passed every year. The Headmaster's role as a controller of reinforcement activities for both teachers and parents. The Headmaster appealed or reminded personally to the teacher or parents for the implementation of reinforcement. The Headmaster also provides opportunities for teachers or parents who face obstacles when applying reinforcement. The Role of the Parents as an extension as well as the balancer of reinforcement when the child is at home. Therefore, the school and parents of Al-Azhar 28 Kindergarten Solo Baru have good communication and conceptualization as a form of reinforcement application to children continuously when children are in school and home environment.Keyword : Reinforcement, Learning to Read Al-Qur’an